PERANCANGAN PENILAIAN KINERJA KARYAWAN PADA PERUSAHAAN FURNITURE DENGAN METODE 360 DEGREES FEEDBACK - Efranto, Remba Yanuar; Riawati, Lely; Dinaputri, Ryanti Setyoningtyas (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2015)
Abstract Performance appraisal is a key factor to develop an effective and efficient. Employees faced with a structured and systematic assessment to measure the achievements of the work.Â Unsatisfaction performance appraisal methods can be a polemical. It happens because of the gap between the expected value to the value of actual performance. Rating scale is one method affected bias and hallo effect.Therefore, it is necessary to design assessment methods better performance. The method of this research is 360 degree feedback. 360 degree feedback is methods in which employees receive confidential, anonymous feedback from the people who work around them.There are 24 employees were assessed in this study.The design competencies and sub-competencies in the performance appraisal form with a 360-degree feedback method prepared by adapting the managerial core competency.Based on 360 degree feedback method, there are many employees who get increased performance assessment compared to the previous assessment method. The increase was influenced by the contribution value of the co-workers, subordinates and themselves.